2019 IEEE 35th International Conference on Data Engineering (ICDE) 2019
DOI: 10.1109/icde.2019.00153
|View full text |Cite
|
Sign up to set email alerts
|

PriSTE: From Location Privacy to Spatiotemporal Event Privacy

Abstract: Location privacy-preserving mechanisms (LPPMs) have been extensively studied for protecting a user's location at each time point or a sequence of locations with different timestamps (i.e., a trajectory). We argue that existing LPPMs are not capable of protecting the sensitive information in user's spatiotemporal activities, such as "visited hospital in the last week" or "regularly commuting between Address 1 and Address 2 every morning and afternoon" (it is easy to infer that Addresses 1 and 2 may be home and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…given observations o 1 , o 2 , · · · , o T and a given user's initial probability π, so that we can directly calculate the Pr(o 1 , o 2 , · · · , o T |EVENT). In Section 4, we will design a mechanism for spatiotemporal event 1. If the Markov model is high-ordered, i.e., the transition matrix has a larger state domain, our approach still works.…”
Section: Overview Of Our Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…given observations o 1 , o 2 , · · · , o T and a given user's initial probability π, so that we can directly calculate the Pr(o 1 , o 2 , · · · , o T |EVENT). In Section 4, we will design a mechanism for spatiotemporal event 1. If the Markov model is high-ordered, i.e., the transition matrix has a larger state domain, our approach still works.…”
Section: Overview Of Our Approachmentioning
confidence: 99%
“…A natural question is whether we can always find an α to release a perturbed location that satisfies Equation (1). The answer is affirmative because α converges exponentially to 0.…”
Section: Case Study 1: Priste With Geo-indistinguishabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Cao et al [9] [11] [12] proposed a method to define the privacy goal, which consisted of spatial and temporal goals. However, even in these studies, it was not mentioned about how to define information such as the place and time.…”
Section: Location Privacy Preference Definitionmentioning
confidence: 99%
“…But the recent studies revealed that k-anonymity might not be rigorous enough since they suffer many realistic attacks [14,16] when the adversary has background knowledge about the original dataset. The recent state-of-the-art location privacy models [3,22,21,20,23,5,6,7] were extended from differential privacy (DP) [10] to private location release since DP is considered a rigorous privacy notion. Although these DP-based location privacy models are rigorously defined, yet they are not flexible and customizable for different scenarios with various requirements on privacy-utility trade-off.…”
Section: Introductionmentioning
confidence: 99%